Testing the Global Community’s Sustainable Development Goals (SDGs) Against Professional Standards and International Law - Lempert, David (Consilience, 2017)
This article examines the global community’s Sustainable Development Goals (SDGs) agenda for 2016 to 2030 by applying several previously published professional and legal indicators, peer-reviewed in a variety of fields, for measuring compliance with international law and professional standards in the social and management sciences for sustainable development, poverty reduction, and development to see how the SDGs do. Overall, the SDGs show little change in substantive, ideological or implementation approach from the previous Millennium Development Goals (MDGs). They are largely a reassertion of 19th and early 20th century European colonial approaches to weaker nations and cultures in violation of many of the principles established under international law for global peace, security and rights following the end of World War II. The implications of this approach, despite the claims, are that the SDGs are likely to further threaten international law objectives for protecting cultural diversity, sovereignty, sustainability and survival in a way that undermines not just international law but also global security.